2012
DOI: 10.1177/1475921712467490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metrics to monitor and compensate for piezoceramic debonding in structural health monitoring

Abstract: This article investigates metrics to assess and compensate for the degradation of the adhesive layer of surface-bonded piezoceramic transducers for structural health-monitoring applications. Capacitance, resonance frequency, and modal damping parameters are derived from admittance curves using a lumped parameter model to monitor the degradation of the transducer adhesive layer. A pitch-catch configuration is then used to discriminate the effect of bonding degradation on actuation and sensing. It is shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 20 publications
(46 reference statements)
0
40
0
Order By: Relevance
“…Common sensor diagnostics procedures using the EM signature are based on the analysis of the susceptance B( f ) [2,11,[29][30][31]. Let B ref ( f ) be the susceptance in the reference healthy case and B unk ( f ) the susceptance in the current unknown state.…”
Section: Electromechanical (Em) Signatures and Associated Metricsmentioning
confidence: 99%
“…Common sensor diagnostics procedures using the EM signature are based on the analysis of the susceptance B( f ) [2,11,[29][30][31]. Let B ref ( f ) be the susceptance in the reference healthy case and B unk ( f ) the susceptance in the current unknown state.…”
Section: Electromechanical (Em) Signatures and Associated Metricsmentioning
confidence: 99%
“…In the case of the work presented by Mulligan et al (2012) the transducers were not degraded, the observed behaviour was attributed to changes occurring to the PZT transducer resonance which moves to lower frequencies as the debonded area increases. The simulation of modal damping shows that it like capacitance decreases gradually with decrease in bonded area, experiment measurements show good correlation with simulation ( (Mulligan et al, 2012), p9).…”
Section: Electromechanical Impedancementioning
confidence: 91%
“…The experimental data suggest that there is alternation between bond area degradation (increase in capacitance) and transducer damage (reduction in capacitance ( (Mulligan et al, 2012), p2). In the case of the work presented by Mulligan et al (2012) the transducers were not degraded, the observed behaviour was attributed to changes occurring to the PZT transducer resonance which moves to lower frequencies as the debonded area increases.…”
Section: Electromechanical Impedancementioning
confidence: 99%
See 2 more Smart Citations